(untitled) - Bettelheim, Frederick A. (Pacific Grove, Calif., 2013)
Helps you to gain foundation in organic chemistry and the chemistry of the human body. This title is designed to make challenging information accessible to everyone. It shows chemistry applied to normal human biochemical pathways and discusses biochemical conditions present in disease.
Keywords: Biochemistry,Sinh hoá học,Chemistry, organic; Hóa hữu cơ